TINJAUAN YURIDIS PERALIHAN HAK TANAH DESA UNTUK KEPENTINGAN UMUM (Studi Kasus Di Desa Ngringo Kecamatan Jaten Kabupaten Karanganyar) - PRAKOSO, ADHITYO BAGUS (Dinamika Hukum, 2015)
The purpose of this research is to study about the implementation of the exchange of village land for the public interest, especially in the village Ngringo, district Karanganyar district Jaten and review of the juridical exchange of village land for public purposes. Background research that the transfer of rights over land in the village Ngringo District of Jaten Karanganyar under Article 15 paragraph (1) of the Regulation of the Minister of Home Affairs No. 4 Year 2007 on the Management of Intellectual village stating that the wealth of the village in the form of village land should not be made a waiver of ownership to the other party, unless used for the public interest. The method used is based on the formulation of the problem and research objectives, consisting of the approach is the problem of dogmatic research is a legal study that looked at the law as a positive norm in the legal system. The data used is secondary data and data collection methods using literature study. Methods of data analysis using the deduction method that stems from the basic principles of a general nature, to be drawn to things that are more specialized. Method of deduction starting from a common law rule on the case at hand. The results of this study is rural land is a potential wealth of the village and the village owned or controlled by the village in accordance with the customs and culture of the local community in order to optimize revenue villages. Changes in the function and status of property ownership village one village land is permitted only on the reasons for government development projects or exchanged for other land more productive or profitable village or release with a more favorable compensation villages so there is no loss to the state. Definition of public interest as defined in Article 15 paragraph (1) Regulation of the Minister of the Interior No. 4 of 2007 on Intellectual village that is described in detail the definition and limitations, thus simplifying the implementation. Keyword : Transitional Rural Land Rights